Exploring Biomass Conversion Technologies: From Raw Materials to Valuable Products - Ali, Syed O; Hashmi, Zubair; Usman, Tanzeel; Muhammad, Atta; Idriss, Ibrahim Maina; Abbas, Syed Hassan; Hassan, Mubashir (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
The global demand for eco-friendly energy has propelled biomass into the spotlight. This report delves into biomass conversion technologies, including biochemical and thermochemical processes, with a focus on hydrothermal conversion. It highlights challenges related to cost-effectiveness and commercial viability. Thermochemical conversion processes, such as pyrolysis and combustion, unlock energy from organic matter. Hydrothermal processing's three approaches and their efficiency are discussed, particularly in biofuels, chemicals, and biochar production. The review analyzes hydrothermal gasification, emphasizing its efficiency and minimal processing time. Carbon and hydrogen gasification efficiencies are crucial in determining gas yields in supercritical conditions. Yield distribution and the influence of feedstock nature and composition on product yield are examined. In conclusion, this report offers insights into biomass conversion technologies and their sustainability for energy and chemical needs.